IDENTIFIKASI FAKTOR PENCEGAH PENULARAN TB PARU DALAM RUMAH DI WILAYAH KERJA PUSKESMAS WONOKUSUMO SURABAYA TAHUN 2016 - Vebrina Arvianti; Umi Rahayu; Khambali . (Poltekkes Kemenkes Surabaya, 2016)
Surabaya ranked the first position for the incident of Pulmonary TB in East Java. In Wonokusumo health center, the number of patients with pulmonary TB increased from 2014 to 2015 by 57% and treatment success rate in 2015 reached 96%. This study aims to determine the relationship of behavior with home sanitation to prevent pulmonary tb infection in the house. This is a Case Control study with study population was family member of patients with pulmonary TB. The sample size was 49 cases and 49 controls. The sampling technique used multistage sampling method. Technique of collecting data used questionnaires and home observation sheets. Data was analyzed by SPSS Chis-Square test. This study shows that ρ (0,000) α (0.05), which means there was relationship between behavior with home sanitation condition to prevent pulmonary TB transmission at home. The conclusion of this study is that family members had poor level of knowledge, attitudes, and sanitation condition. 61.2% did not meet the standard and there was relationship of behavior and home sanitation. the society should add information about pulmonary TB condition and home sanitary as well as conducting routine mass cleaning program. Wonokusumo health center needs to provide counseling and formation of cadres that serves to provide information and motivation to pulmonary TB patients. Keywords : Behavior, home sanitation condition, pulmonary tuberculosis